The Impacts of Using Smartphone Dating Applications on Sexual Risk Behaviours in College Students in Hong Kong - Choi, Edmond Pui-Hang; Wong, Janet Yuen-Ha; Lo, Herman Hay-Ming; Wong, Wendy; Chio, Jasmine Hin-Man; Fong, Daniel Yee-Tak (PLOS ONE, 2016)
Dating applications (apps) on smartphones have become increasingly popular. The aim of this study was to explore the association between the use of dating apps and risky sexual behaviours. Data were collected in four university campuses in Hong Kong. Subjects completed a structured questionnaire asking about the use of dating apps, sexual behaviours, and sociodemographics. Multiple linear and logistics regressions were used to explore factors associated with sexual risk behaviours. Six hundred sixty-six subjects were included in the data analysis. Factors associated with having unprotected sexual intercourse with more lifetime sexual partners included use of dating apps (β = 0.93, p<0.01), having one’s first sexual intercourse before 16 years of age (β = 1.74, p<0.01), being older (β = 0.4, p<0.01), currently being in a relationship (= 0.69, p<0.05), having a monthly income at least HKD$5,000 (β = 1.34, p<0.01), being a current smoker (β = 1.52, p<0.01), and being a current drinker (β = 0.7, p<0.01). The results of a multiple logistic regression analysis found that users of dating apps (adjust odds ratio: 0.52, p<0.05) and current drinkers (adjust odds ratio: 0.40, p<0.01) were less likely to have consistent condom use. Users of dating apps (adjust odds ratio: 1.93, p<0.05), bisexual/homosexual subjects (adjust odds ratio: 2.57, p<0.01) and female subjects (adjust odds ratio: 2.00, p<0.05) were more likely not to have used condoms the last time they had sexual intercourse. The present study found a robust association between using dating apps and sexual risk behaviours, suggesting that app users had greater sexual risks. Interventions that can target app users so that they can stay safe when seeking sexual partners through dating apps should be developed.